Application of Kohut in Public Mental Health: Understanding Fatima - Julia Jamaludin (Psychotherapy and Counselling Journal of Australia)
In the current Australian public mental health system, in which scarce resources result in a ‘revolving door’ system, pharmacological intervention conveniently takes precedence over its psychological counterpart. Although there is limited capacity for psychodynamic psychotherapy intervention in the public mental health system, I believe many patients could be understood and better managed through psychotherapy, even if it is adapted as an adjunct to biological psychiatry. This case report illustrates the applicability of Kohut’s self psychology principles in approaching psychopathology in the public setting. It is based on the experience of a psychiatry registrar in a public acute inpatient mental health unit which cares for more severe psychiatric patients. It aims to demonstrate the importance of empathic understanding and exchanges within therapeutic relationships, as argued by Kohut, especially in those forced and compromised by involuntary treatment orders, as with most patients encountered in the public setting, exemplified by the case of Fatima.